Calculation of Cost Estimation Based on Building Information Modeling in Construction Projects - Mahendra, Muhamad Yusuf; Kartika, Nia; Tahadjuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
BIM (Building Information Modeling) is currently a concept that can include important information in planning. This study aims Kosmetika Global Helath Indonesia, Ejip Area, Cikarang. In this research, 3D modeling of steel structures was carried out based on shop drawing documents from the research location. Next, calculate the quantity take-off for the estimated cost of steel structure work using Autodesk Revit software. It can be concluded that using Auusingit software can optimize the 2D modeling process into the 3D form so that the quantity take-off calculations can be more detailed and accurate and reduce material waste. It also already supports BIM 5D to help calculate estimated costs. The results of calculating estimated costs using Autodesk Revit software are 3.45% smaller than conventional calculations. It is because conventional methods are calculated manually based on 2D images, which allow for differences due to lack of detail.